2015
DOI: 10.1007/978-3-319-16640-7_3
|View full text |Cite
|
Sign up to set email alerts
|

Potentials of Exploiting Heterotrophic Metabolism for Biodiesel Oil Production by Microalgae

Abstract: The current prices of microalgae oils are much higher than oils from higher plants (vegetable oils) mainly due to the high cost of photoautotrophic cultivation of microalgae. However, many strains of microalgae can also grow and produce oil using organic carbons, as the carbon source under dark (heterotrophy) or light conditions (mixotrophy). Lipid productivities of most strains of microalgae are higher in culture systems that incorporate heterotrophic metabolisms (presence of organic carbon source) than under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 105 publications
2
6
0
Order By: Relevance
“…Under heterotrophic cultivation, biomass concentrations were higher for both glucose and glycerol-supplemented media than those obtained in photoautotrophic cultures. This supports the argument that heterotrophic cultures yield more biomass than their autotrophic counterparts [9] [15]. Another major advantage of heterotrophic cultures over the photoautotrophic culture is that it is simpler and cheaper to construct and operate large scale heterotrophic reactors than photobioreactors since light supply and distribution is a big constraint in photobioreactor design and scale up [35].…”
Section: Heterotrophic Cultivation Of Chlorella Lewinii Sub3545914 Onsupporting
confidence: 71%
See 2 more Smart Citations
“…Under heterotrophic cultivation, biomass concentrations were higher for both glucose and glycerol-supplemented media than those obtained in photoautotrophic cultures. This supports the argument that heterotrophic cultures yield more biomass than their autotrophic counterparts [9] [15]. Another major advantage of heterotrophic cultures over the photoautotrophic culture is that it is simpler and cheaper to construct and operate large scale heterotrophic reactors than photobioreactors since light supply and distribution is a big constraint in photobioreactor design and scale up [35].…”
Section: Heterotrophic Cultivation Of Chlorella Lewinii Sub3545914 Onsupporting
confidence: 71%
“…[10] [11] [14] [15] [34]. Similarly, lipid accumulation in heterotrophic cultures was significantly higher than the values obtained in photoautotrophic cultures.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…This attribute is vital since the heterotrophic cultivation of algae has been recommended for biofuel production in terms of the cost of production. It has been pointed out previously that one major challenge of the use of algae for bioenergy is that many species cannot grow heterotrophically [9] [10].…”
Section: Discussionmentioning
confidence: 99%
“…Not all oils are suitable for biodiesel production de novo. Ogbonna and McHenry [9] and Ogbonna and Moheimani [10] reported that oil quality of heterotrophically cultivated algal cells is better than those under photoautotrophic…”
Section: Introductionmentioning
confidence: 99%